BPC em disputa: Como alteraç\~oes regulatórias recentes se refletem no acesso ao benefício - Andrea Barreto De Paiva; Marina Brito Pinheiro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– This study investigates recent changes in the Benefício de Prestaç\~ao Continuada (BPC) policy and discusses its advances and limitations in guaranteeing and promoting rights. In addition to briefly analyzing the trajectory of changes in the BPC eligibility criteria between 1996 and 2016, the work focuses on initiatives to modernize the management of BPC, such as mandatory registration in CadÚnico, INSS Digital implantation, and new procedures for revising and updating beneficiary registration. The study also discusses the changes resulting from Law no 13.982/2020, approved by the National Congress at the beginning of the Covid-19 pandemic, as well as new administrative and regulatory measures presented by the Executive Power in the context of the pandemic public policy response. Finally, the authors point to the need for a balance between strategies for policy improving, increasing state efficiency and guaranteeing the BPC's primary function of offering protection to a population in a situation of great vulnerability.
Keywords: I38; 330; social assistance policies; Benefício de Prestaç\~ao Continuada; social protection systems